International Spillovers of (Un)Conventional Monetary Policy: The Effect of the ECB and US Fed on Non-Euro EU Countries - Jan Hajek; Roman Horvath (Charles University in Prague, Institute of Economic Studies (IES), 2017)
We estimate a global vector autoregression model to examine the effects of euro area and US monetary policy stances, together with the effect of euro area consumer prices, on economic activity and prices in non-euro EU countries using monthly data from 2001-2016. Along with some standard macroeconomic variables, our model contains measures of the shadow monetary policy rate to address the zero lower bound and the implementation of unconventional monetary policy by the European Central Bank and US Federal Reserve. We find that these monetary shocks have the expected qualitative effects but their magnitude differs across countries, with Southeastern EU economies being less affected than their peers in Central Europe. Euro area monetary shocks have greater effects than those that emanate from the US. We also find certain evidence that the effects of unconventional monetary policy measures are weaker than those of conventional measures. The spillovers of euro area price shocks to non-euro EU countries are limited, suggesting that the law of one price materializes slowly.
Keywords: E52; E58; 330; International spillovers; monetary policy; global VAR; shadow rate